The Unseen Web, an Enormous Mass of Internet: Sundus Munir - SUNDUS MUNIR, SUNDUS MUNIR; Afrozah Nadeem, Afrozah Nadeem; Syeda Binish Zahra, Syeda Binish Zahra; sadia kousar, sadia kousar (International Journal for Electronic Crime Investigation, 2020)
Deep web is the part of the internet; it holds 99% of the internet rest of the internet is known assurface web and it is access able by standard search engines, Deep web is famous by different namesand can be called as invisible and hidden web but it can’t be accessed by the standard exploratoryengines this is due to the un indexed contents by common exploratory engines. Deep web content isinvisible under HTML form. Deep web provides anonymous internet platform for hackers, governmentagencies and others. Due to this no one can trace the location of the user and don’t have anykind of information about the web surfing of the user. Dark web is the part of Deep web, the reasonbehind it commonly used for the black market i.e. Drug sale, ammunition sale, and many otherillegal activities. It is the consist of millions of websites some of which are very informative. Whileon the other hand some of the portion is legal to visit and rest is illegal. These websites can beaccessed by using the popular tools, i.e. TOR, I2P which provide anonymity. About 2 million peopleuse the TOR browser to browse deep and dark web.